JS-WHL-ISH-RTSL-2: WHY SHOULD WE WORRY ABOUT SODIUM INTAKE, IF WE INCLUDE A DIURETIC IN THE HYPERTENSION TREATMENT REGIMEN ?. (January 2023) - Lackland, Daniel T
Abstract : The causal role of sodium intake on blood pressure level has been long recognized. While the pathophysiological link between hypertension and cardiovascular, cerebrovascular, and renal disease events are clear, there is evidence that sodium has an independent direct effect on target organs through multiple mechanisms including vascular damage, oxidative stress, hormonal alterations, the immune system and the gut microbiome. Thus, reduction in salt and sodium intake is an important global strategy to reduce disease burden. Certainly sodium is an essential element for homeostasis, but the levels of consumption far exceed the amount needed for physiological function. Likewise, considerable evidence indicates reduction in sodium consumption is associated with significant reduction in blood pressure in all individuals at the population level. Individual response to sodium intake is variable, but should be considered a risk factor when consumption is excessive. Interventions such as the DASH-sodium (Dietary Approaches to Stop Hypertension) study has clearly demonstrated benefit from sodium reduction. In nearly all populations acculturated to an industrialized lifestyle, blood pressure increases with age resulting with an increasing hypertension prevalence. Thus, salt intake becomes increasingly relevant at all ages.. Nonetheless the levels of salt consumption that are recommended remain debated. Contributing to the varying study results are the individual differences in salt sensitivity. Therefore, for salt-sensitive risk groups in the population, stricter limits of salt consumption should be implemented, with a specific target to the young before target organ damage. Maximum prevention benefit for reduced sodium consumption should target children. The magnitude of blood pressure lowering achieved with sodium reduction has a dose-response relationship with greater impact in older, non-white, and hypertensive populations. Many factors contribute to blood pressure and risk reduction with salt consumption leading to unclear and less precise results and conclusions. Individuals with salt-sensitive hypertension and/or low-renin hypertension typically have factors conducive to treatment with a diuretic. As salt-sensitive hypertension is more common in black patients, older adults, patients with more severe hypertension, and patients with co-morbidities, diuretics have been shown to be particularly effective with salt reduction adding additional benefit.